Copper Induction of Laccase Isoenzymes in the Ligninolytic Fungus Pleurotus ostreatus - Palmieri, Gianna (American Society for Microbiology, 2000)
Pleurotus ostreatus is a white rot basidiomycete that produces several extracellular laccase isoenzymes, including phenol oxidase A1b (POXA1b), POXA2, and POXC. POXC was the most abundant isoenzyme produced under all of the growth conditions examined in this study. Copper was the most efficient inducer of laccase activity among the putative inducers tested. The amounts of all of the previously described laccase isoenzymes increased substantially in copper-supplemented cultures. Under these conditions expression of POX isoenzymes was regulated at the level of gene transcription. It is worth noting that poxa1b mRNA was the most abundant induced transcript at all of the growth times analyzed, and the amount of this mRNA increased until day 7. The discrepancy between the poxa1b transcript and protein amounts can be explained by the presence of a high level of the protein in P. ostreatus cellular extract, which indicated that the POXA1b isoenzyme could be inefficiently secreted and/or that its physiological activity could occur inside the cell or on the cell wall. Moreover, the POXA1b isoenzyme behaved uniquely, as its activity was maximal on the second day of growth and then decreased. An analysis performed with protease inhibitors revealed that the loss of extracellular POXA1b activity could have been due to the presence of specific proteases secreted into the copper-containing culture medium that affected the extracellular POXA1b isoenzyme.